If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying e + -27 = 19 Reorder the terms: -27 + e = 19 Solving -27 + e = 19 Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '27' to each side of the equation. -27 + 27 + e = 19 + 27 Combine like terms: -27 + 27 = 0 0 + e = 19 + 27 e = 19 + 27 Combine like terms: 19 + 27 = 46 e = 46 Simplifying e = 46
| 2x^2-40x=0 | | b+14=33 | | 4y^2+31y-8=0 | | d-41=34 | | 14(x-2)-4=12x+2 | | 3(-2u^2+5)= | | y^3-6y^2+8y=0 | | 8x+4(x-3)=4(6x+4)-4 | | -12.84-1.5t=2.7(t+3.8) | | 9-9=14 | | 7(x+3)=13x-12 | | 64r^2=64 | | 3.9x+88=6.4x+8 | | 6-2x-3=4 | | 4a+3(2a-2)=44 | | n(n)-4n+1=5 | | x+21=29 | | 5f+4+f=52 | | 7x-8=3x+16 | | 12+q(5-q)-5q=0 | | -.37x+2=0 | | 7x+8=3x-16 | | 3m+4m=21 | | 20x+50=250 | | x+1-5=6 | | 13x+6=6x-1 | | 4x+2=8x-7 | | 4y+11=7y-28 | | q=0.25p^2-14 | | 5d=95 | | -7x+18=1x-36 | | x^2-7*x+12=0 |